The Egyptian Heracles of Gades. - Álvarez-Martí-Aguilar, Manuel (CNR Edizioni, 2024)
Melqart, the tutelary god of the Phoenician city of Gades, is referred to by Greek and Latin authors of the Roman period as Heracles or Hercules. Although several of these authors recognise his Tyrian origin, Pomponius Mela and Philostratus refer to the god as “Egyptian”. Accordingly, the aim here is to investigate the reasons behind the “Egyptian” character of the Melqart/Heracles worshipped in Gades, a traditionally enigmatic question. One of the possible reasons for this attribution may be the Egyptianising character of the representations of Phoenician divinities, including Melqart. However, some authors, such as Silius Italicus and Philostratus himself, report the absence of cult images of the god in his sanctuary at Gades. This raises the possibility that the “Egyptian” character of the Heracles/Hercules of Gades in Roman times might have been more related to the connotations of the mythical deeds of the god in the confines of the oecumene, which included measuring the world to its limits, protecting the community from catastrophic floods and the use of cosmic magic, aspects that in Hellenistic and Roman times were related to Egyptian wisdom.
Permiso editorial en petición 50/2025 gestor de peticiones RIUMA
Keywords: Religión fenicia; Religión egipcia; Civilización antigua; Gades; Melqart; Fenicios; Magia antigua; Heracles egipcio